Penetrating ocular fish hook injury: a case report - Chakraborti, Chandana; Mukhopadhya, Udayaditya; Mazumder, Dayal Bandhu; Tripathi, Partha; Samanta, Swapan Kumar (Nepalese Journal of Ophthalmology, 2016)
Background: Fishing is a popular rural recreational activity. Fortunately, penetrating ocular injuries with fish hooks are rare. These injuries are usually caused by fish hook prongs penetrating the ocular tissues. We report a rare case of penetrating fish hook injury to the globe and its successful surgical management.Case: A 12- year-old female child was referred to the causality with a fish hook embedded in her right eye. She sustained the injury while fishing with her father. The fish hook had penetrated the globe obliquely. The hook was removed via its entrance wound under general anesthesia. Subsequently the child developed traumatic cataract which was operated with a final visual outcome of 6/12. Conclusion: Visual prognosis can be profoundly affected by the initial management. Prompt surgical intervention as done in our case is recommended to prevent significant visual loss.